Validation of the Brazilian version of the Halitosis Associated Life-Quality Test (HALT) - Juliana Oliveira da SILVEIRA; Luís Otávio Miranda COTA; Cristiane Baccin BENDO; Sandro Felipe Santos FARIA; Fernando Oliveira COSTA (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract The present study aimed to validate (cross-culturally adapt and test psychometric properties) the Brazilian version of the Halitosis Associated Life-Quality Test (HALT). A process of translation and cross-cultural adaptation was conducted by a group of dental researchers. The first draft of the Brazilian Portuguese version was pre-tested on a sample of 33 individuals leading up to the final version of the questionnaire. The Brazilian version of the HALT (B-HALT) was applied to 100 individuals with halitosis (organoleptic score ≥ 2) and 100 individuals without halitosis (organoleptic score < 2). Exploratory factor analysis (EFA) was performed to evaluate the dimensionality of B-HALT. Cronbach's alpha (α) and interclass correlation coefficient (ICC) were used to measure its reliability. For convergent validity, Spearman's correlation was conducted between the B-HALT and the organoleptic scores. The discriminant validity was evaluated through the Mann-Whitney and Kruskal-Wallis tests. EFA confirmed the unidimensionality of B-HALT, which has also demonstrated excellent internal consistency (α = 0.96) and test-retest reliability (ICC = 0.93). There was a positive correlation between B-HALT and organoleptic scores (r = 0.33; p < 0.001). B-HALT was able to discriminate between the groups with and without halitosis measured by the organoleptic method (p < 0.001) and self-reported halitosis (p < 0.001). B-HALT has demonstrated to be a reliable and valid tool to evaluate the oral health-related quality of life associated to halitosis in Brazilian adults.